Different expression patterns of VISTA concurrent with PD-1, Tim-3, and TIGIT on T cell subsets in peripheral blood and bone marrow from patients with multiple myeloma - Huang, Shuxin; Zhao, Yujie; Liao, Pengjun; Wang, Jinghua; Li, Zhiyan; Tan, Jiaxiong; Zha, Xianfeng; Chen, Shaohua; Li, Yangqiu; Zhong, Liye (Frontiers in Oncology, 2022)
V-type immunoglobulin domain-containing suppressor of T cell activation (VISTA) is considered as an immunosuppressive factor and potential therapeutic target for anticancer therapy. However, little is known about VISTA expression and its role in immunosuppression in multiple myeloma (MM). In this study, VISTA expression and co-expression with programmed cell death receptor-1 (PD-1), T cell immunoglobulin mucin-domain-containing-3 (Tim-3), and T cell immunoglobulin and ITIM domain (TIGIT) in CD3+, CD4+, CD8+, and regulatory T (Treg) cells were analyzed in patients with MM by multi-color fluorescent flow cytometry of peripheral blood (PB) and bone marrow (BM) samples from 36 patients with MM and compared to 36 PB samples and 10 BM samples from healthy individuals (HIs), which served as controls. The results demonstrated a significant increased percentage of VISTA co-expression with PD-1, Tim-3, and TIGIT in CD3+, CD4+, CD8+, and Treg cells in PB from MM patients compared with HIs. A similar trend for VISTA+CD8+ T cells was found in BM. Moreover, a trend of a high percentage on VISTA expression and co-expression in PB rather than BM was found. Furthermore, significant positive correlations existed for VISTA expression concurrent with PD-1, Tim-3, and TIGIT in T cell subsets and clinical indicators, including Revised International Staging System (R-ISS) staging of multiple myeloma, Eastern Cooperative Oncology Group (ECOG) score, and beta-2-microglobulin (β2-MG). In conclusion, higher VISTA expression concurrent with PD-1, Tim-3, and TIGIT on T cells, particularly in the PB of patients with MM, may result in T cell exhaustion and dysfunction and be closely associated with disease progression and clinical indicators. Thus, VISTA may be considered a potential target for reversing T cell exhaustion and improving T cell function in MM.